Reovirus polypeptide sigma 3 and N-terminal myristoylation of polypeptide mu 1 are required for site-specific cleavage to mu 1C in transfected cells. - Tillotson, L (1992)
N-myristoylated viral polypeptide mu 1 was produced in COS cells transfected with a transient expression vector containing a DNA copy of the reovirus M2 gene. The mu 1 product was specifically cleaved to polypeptide mu 1C in cells that were cotransfected with the reovirus S4 gene and that expressed polypeptide sigma 3. Studies with site-specific mutants of the M2 gene demonstrated that conversion of mu 1 to mu 1C was dependent on myristoylation and the presence of the proteolytic cleavage sequence asparagine 42-proline 43 in mu 1, as well as on the presence of polypeptide sigma 3. The mu 1C product and polypeptide sigma 3 formed complexes that were immunoprecipitated by sigma 3-directed antibody, and a myristoylation-negative M2 double mutant, G2A-N42T, yielded mu 1 that did not undergo cleavage to mu 1C or bind sigma 3. However, the N42T single mutant did form immunoprecipitable complexes with sigma 3, indicating that binding can occur in the absence of cleavage. Polypeptide sigma 3 alternatively can bind double-stranded RNA and in COS cells stimulates translation of reporter chloramphenicol acetyltransferase mRNA translation, presumably by blocking double-stranded RNA-mediated activation of the eukaryotic initiation factor 2 alpha subunit kinase which inhibits the initiation of protein synthesis. Consistent with these observations and with the formation of mu 1C-sigma 3 complexes, coexpression of M2 with S4 DNA prevented the translational stimulatory effect of polypeptide sigma 3.